Improvement of Nanopore sequencing provides access to high quality genomic data for multi-component CRESS-DNA plant viruses - Daniel H. Otron; Denis Filloux; Andy Brousse; Murielle Hoareau; Babbitha Fenelon; Cécile Hoareau; Emmanuel Fernandez; Fidèle Tiendrébéogo; Jean-Michel Lett; Justin S. Pita; Philippe Roumagnac; Pierre Lefeuvre (Virology Journal)
Abstract Background Faced with the recrudescence of viral CRESS-DNA plant diseases, the availability of efficient and cost-effective tools for routine diagnosis and genomic characterisation is vital. As these viruses possess circular single-strand DNA genomes, they have been routinely characterised using rolling circle amplification (RCA) coupled with Sanger sequencing. However, while providing the basis of our knowledge of the diverse CRESS-DNA viruses, this approach is laboratory-intensive, time-consuming and ultimately ineffective faced with co-infection or viruses with multiple genomic components, two common characteristics of these viruses. Whereas alternatives have proved effective in some applications, there is a strong need for next-generation sequencing methods suitable for small-scale projects that can routinely produce high quality sequences comparable to the gold standard Sanger sequencing. Results Here, we present an RCA sequencing diagnostic technique using the latest Oxford Nanopore Technology flongle flow cells. Originally, using the tandem-repeat nature of RCA products, we were able to improve the quality of each viral read and assemble high-quality genomic components. The effectiveness of the method was demonstrated on two plant samples, one infected with the bipartite begomovirus African cassava mosaic virus (ACMV) and the other infected with the nanovirus faba bean necrotic stunt virus (FBNSV), a virus with eight genomic segments. This method allow us to recover all genomic components of both viruses. The assembled genomes of ACMV and FBNSV shared 100% nucleotide identity with those obtained with Sanger sequencing. Additionally, our experiments demonstrated that for similar-sized components, the number of reads was proportional to the segment frequencies measured using qPCR. Conclusion In this study, we demonstrated an accessible and effective Nanopore-based method for high-quality genomic characterisation of CRESS-DNA viruses, comparable to Sanger sequencing. Face with of increasing challenges posed by viral CRESS-DNA plant diseases, integrating this approach into routine workflows could pave the way for more proactive responses to viral epidemics.